Aktivitas Antioksidan dan Antimikrobial dari Ekstrak Plectranthus amboinicus - Penelitian Farmasi Indonesia (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2012)
Plectranthus amboinicus or bangun-bangun is a traditional medicinal plant used for postpartum recovery in North Sumatera. The aims ofthis study were to detemine antioxidant and antimicrobial activity of leaves Plectranthus amboinicus. The leaves of Plectranthus amboinicuswere extracted with using n-hexane, ethyl acetate and methanol, successively. The extracts were tested to antioxidant activity assay usingDPPH with two fold dillution tehnique and ascorbic acid was used as standard. The antimicrobial activity was conducted using agar diffusionmethod against Escherichia coli, Staphylococcus aureus and Candida albicans. The Amoxsan used as positive control for antibacterialassay, while ketokenazole was for antifungi test. Extracted solvents were used as negative control. The n-hexane and ethyl acetate extractsdid not show any antioxidant activity. While, the IC50 free radical DPPH of methanol extract was 90.96 mg/mL and ascorbic acid was 58.792mg/mL. The antimicrobial activity of n-hexane and Amoxsan againts Escherichia coli were 11.95 and 7.53 mm. The inhibition zone againtsStaphylococcus aureus were 11.30 and 11.57 mm. The antimicrobial activity of ethyl acetate and Amoxsan againts Escherichia coli were12.29 and 7.71 mm. The inhibition zone against Staphylococcus aureus were 13.72 and 11.57 mm. The n-hexane and ethyl acetate did notshow any antifungi activity towards Candida albicans. The methanol extract did not show any inhibition zone againts the selectedpathogens.